2018
DOI: 10.1002/hep4.1239
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double‐Blind, Placebo‐Controlled, Single Ascending Dose Trial of Synthetic Preimplantation Factor in Autoimmune Hepatitis

Abstract: Preimplantation factor (PIF) is an evolutionary conserved peptide secreted by viable embryos which promotes maternal tolerance without immune suppression. Synthetic PIF (sPIF) replicates native peptide activity. The aim of this study was to conduct the first‐in‐human trial of the safety, tolerability, and pharmacokinetics of sPIF in patients with autoimmune hepatitis (AIH). We performed a randomized, double‐blind, placebo‐controlled, prospective phase I clinical trial. Patients were adults with documented AIH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Other experimental strategies are aimed at increasing the pool and function of regulatory T‐cells, 49 for example by subcutaneous low‐dose interleukin‐2, which has proved to reduce inflammatory liver damage 50 , 51 . A phase I trial with subcutaneous synthetic preimplantation factor showed good safety and tolerability in AIH patients, but was not continued into phase II (source: NCT03593460) 52 …”
Section: Future Prospectsmentioning
confidence: 99%
“…Other experimental strategies are aimed at increasing the pool and function of regulatory T‐cells, 49 for example by subcutaneous low‐dose interleukin‐2, which has proved to reduce inflammatory liver damage 50 , 51 . A phase I trial with subcutaneous synthetic preimplantation factor showed good safety and tolerability in AIH patients, but was not continued into phase II (source: NCT03593460) 52 …”
Section: Future Prospectsmentioning
confidence: 99%
“…Animal models of AD are currently being prepared but are beyond the scope of this manuscript. However, sPIF received a FDA Fast-Track Approval for first-in-human Phase I trial and orphan drug designation for autoimmunity, which was successfully completed [ 35 ]. Such observations together with the current evidence support PIF's potential protective role in AD or type II diabetes, where IDE plays a major role.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐implantation factor was awarded FAST‐TRACK status by the FDA, and a phase I placebo‐controlled study of pre‐implantation factor administration in 18 patients with AIH demonstrated minimal toxicity 126 . Pre‐implantation factor may now be taken forward to efficacy trials and represents a potential novel therapy for AIH, although a phase 2 trial was announced and then withdrawn as the manufacturer reported a change in the focus of drug development.…”
Section: Novel Therapies Undergoing Clinical Assessment In Aihmentioning
confidence: 99%
“…The advantages of pre‐implantation factor are that it is a naturally occurring peptide, with no evidence of anti‐pre‐implantation factor antibody formation in the phase I study. The required dosing interval is currently unknown, although with a half‐life of 91 minutes, 126 frequent subcutaneous dosing may be required.…”
Section: Novel Therapies Undergoing Clinical Assessment In Aihmentioning
confidence: 99%